Valoración nutricional del pasto KING GRASS (Pennisetum purpureum x pennisetum typhoides) IN VITRO a tres niveles de fertilización nitrogenada y época de corte - Serrano Ávila, Junior Edmundo; Salazar Dávila, Tania Lorena (Calceta: Espam, 2010)
RESUMEN El presente trabajo se ejecutó en el campus Politécnico de la ESPAM que se encuentra ubicada a 0º50’39’’ de Latitud Sur y 80º9’33’’ de Longitud Oeste, a una altitud de 58 msnm. El objetivo principal de esta investigación consistió en incrementar la productividad y calidad del pasto King grass mediante la fertilización nitrogenada y época adecuada de corte. Tomando como referencia el campo de trabajo de la Espam “MFL” . Se utilizó un Diseño de bloques completamente al azar. Los mejores resultados de forraje verde fueron en los tratamientos en que se efectuaron aplicaciones de fertilizante con nitrógeno, constituyéndose en el de mayor rendimiento el tratamiento con la interacción de 230 kilos de nitrógeno por hectárea/año y 60 días con 121123 kilos de forraje verde por corte por hectárea año. El tratamiento que reportó mayores valores en la variable materia seca fue en la interacción de 230 kilos de nitrógeno hectárea/año y 60 días de corte con 5480 kilos de materia seca por corte por hectárea año. La fertilización con nitrógeno en el pasto King grass influyó positivamente sobre el contenido de proteína, es así que los tratamientos que recibieron fertilización respondieron positivamente en comparación con el testigo, siendo el tratamiento con mayor porcentaje de proteína la interacción de 230 kilos de nitrógeno hectárea/año y 30 días de corte, con 12.46% de proteína. La variable fibra fue superior en el tratamiento testigo, reportando 37.10 % de fibra a los 60 días de corte. El tratamiento que reportó el menor valor de esta variable fue la interacción de 230 de kilos de nitrógeno por hectárea/año y 30 días de corte.
SUMMARY The present work was executed in the Polytechnic campus of the ESPAM that is located at 0º50'39 '' of South Latitude and 80º9'33 '' of Longitude West, to an altitude of 58 msnm. The main objective of this investigation consisted on increasing the productivity and quality of the grass King grass by means of the fertilization nitrogenada and appropriate time of court.. Taking like reference the field of work of the Espam " MFL ". A Design of blocks was used totally at random. The best results of green forage were in the treatments in that fertilizer applications were made with nitrogen, being constituted in that of more yield the treatment with the interaction of 230 kilos of urea for hectárea/año and 60 days with 121123 kilos of green forage for court for hectare year. The treatment that I report bigger values in the variable dry matter was in the interaction of 230 kilos of nitrogen hectárea/año and 60 days of court with 5480 kilos of dry matter for court for hectare year. The fertilization with nitrogen in the grass King grass influenced positively on the protein content, it is so the treatments that you/they received fertilization they responded positively in comparison with the witness, being the treatment with more protein percentage the interaction of 230 kilos of urea hectárea/año and 30 days of court, with 12.46 protein%. The variable fiber was superior in the treatment witness, reporting 37.10 fiber% to the 60 days of court. The treatment that reported the smallest value in this variable was the interaction of 230 of kilos of nitrogen for hectárea/año and 30 days of court. The digestibilidad of the grass King grass was influenced by the fertilization nitrogenada and state fenológico of the plant, being the treatment with better digestibilidad value the interaction of 230 kilos of nitrogen hectárea/año and 30 days of court, with 71.80 digestibilidad%. The treatment that reported bigger value in energy metabolizable was in the interaction of 230 kilos of urea hectare year and 30 days of court with 1.99 Mcal/kg matter was of energy metabolizable. Regarding the economic analysis the treatment with better profitable benefits was that of 230 kilos of nitrogen hectare year; with a gain of $0.89, for each invested dollar, equivalent to 89% of profitability.
Keywords: Fertilización con nitrógeno; Estación experimental; Madurez de la planta; Materia seca